Political thinkers : from Socrates to the present - Kelly, Paul (ed.); Boucher, David (ed.) (New Delhi, 2016)
Thinking about politics or political thought, which is an activity almost as old as politics itself, comprises a huge variety of styles and approaches. Political thinkers have sought to explain institutions and practices, advise rulers, defend values and principles, or criticize the world in which they found themselves. They have focused narrowly on institutions of government, lawmaking, and the exercise of coercive power, or more broadly on the character of a society or people. At its most general, political thought converges with what we now describe as eth ics and moral philosophy, sociology and anthropology, as well as theology and metaphysics. Some political thinkers have sought to explain the nature of man as a political animal and the role of politics in an account of human flourishing and well-being, and thus assert the dignity of political activity in fully human life. Others have sought to explain why politics, though necessary, is secondary to more important human goals such as seeking salvation and eternal life. More recently other thinkers have sought to subsume political activity beneath realms of human activity such as 'society' or 'the economy. This variety or plurality of styles, approaches, and presuppositions has made political thought an exciting intellectual activity for students and scholars alike, as well as making general surveys of the character of political thought a matter of deep and persistent conflict among them. As approaches to theorizing about politics differ, so do accounts of how and why we should continue to study political thought. It is therefore incumbent upon us, in presenting a revised second edition of this overview of some of the main Western political thinkers from ancient Greece to the present, to say something, by way of introduction, both about the activity and point of political thinking and about those thinkers we have included in this book.
Keywords: Political Science